Você gosta de alguém? Representações de amor, erotismo e sexo construídas por crianças em contextos populares a partir da cultura midiática - Martins, Jaqueline Sobral Mesquita (2014)
Children´s increasing access to media and their exposure to a highly eroticized culture has created and originated controversial debate between researchers, educators as well as parents who very often blame the media for destroying childhood . Based on paradigms that perceive the child as an active actor, despite still in developing state, but capable of dialoguing, influencing and being influenced by the adult world, and also capable of producing their own culture and constructing their own meanings, this research aims at understanding the social uses and appropriations that this particular audience makes of media content. It also looks at how these mediatized contents influence their perceptions of love, eroticism and sex. The study depicts results of an audience study, along with ethnographic method, conducted in a group of working class children, aged between 7 and 11 years old who attend educative activities at a Non-Governmental Organization (NGO) which offers community care for children in the west region of the city of Sao Paulo, Brazil.